Curative liver transplantation after lung resection for advanced hepatocellular carcinoma with lung metastasis and inferior vena cava tumor thrombosis: a case report - Dong Jin Joo; Do Young Kim; Jinsil Seong; Hyun Jeong Kim; Jae Geun Lee; Dai Hoon Han; Gi Hong Choi; Myoung Soo Kim; Jin Sub Choi; Soon Il Kim (Korean Liver Cancer Association, 2021)
Hepatocellular carcinoma (HCC) with distant metastasis is an absolute contraindication for liver transplantation (LT). However, it is still unclear whether LT is feasible or acceptable in such patients, albeit after being treated with a multidisciplinary approach and after any metastatic lesion is ruled out. We report one such successful treatment with living donor LT (LDLT) after completely controlling far-advanced HCC with inferior vena cava tumor thrombosis and multiple lung metastases. The patient has been doing well without HCC recurrence for eight years since LDLT. The current patient could be an anecdotal case, but provides a case for expanding LDLT indications in the context of advanced HCC and suchlike.